EVALUASI DAYA DUKUNG TANAH DASAR (SUBGRADE) PADA PERKERASAN JALAN MENGGUNAKAN ALAT DYNAMIC CONE PENETROMETER - Fithriyah Patriotika; Chintya Aprilia (Jurnal Applied Science in Civil Engineering, 2025)
Abstract: This Final Project aims to evaluate the bearing capacity of the subgrade on road pavement on Jl. Koto Tuo, Koto Tangah District, Padang City using the Dynamic Cone Penetrometer (DCP) method. This Final Project focuses on field testing by taking 10 points along the road for ±1 km in a zigzag manner. In addition to the DCP test, tests on the physical properties of the original soil such as water content, specific gravity, sieve analysis, and hydrometer were also carried out to obtain a comprehensive picture of the subgrade soil characteristics. The test results showed that the field CBR value ranged from 1.46% to 2.04%, indicating that the bearing capacity of the subgrade was relatively low and did not meet the minimum CBR standard of 6% according to SNI standards. The characteristics of the soil at the data collection location were classified as non-organic silty clay with low plasticity (CL-ML) and included in the AASHTO classification group A-2-4. The results of the soil physical properties test showed an average water content of 15.87% and an average specific gravity of 2.614 which also affected the strength of the subgrade. Various technical recommendations include the need for re-compacting the subgrade, using reinforcement materials such as geotextiles, and improving road maintenance to reduce further damage.